Growth and timber quality evaluation of 33 European beech (Fagus sylvatica L.) provenances from a site in Southern Sweden - Bergkvist, John (SLU/Southern Swedish Forest Research Centre, 2019)
This study aims to shed more light on the differences in growth and timber quality characteristics between European beech provenances at its northern distribution margin. Data was collected from a provenance trial established in 1998 in southern Sweden to determine the growth and development of 33 provenances of European beech (Fagus sylvatica L.) originating from within Europe. A generalized linear mixed model with a post-hoc Tukeys' test was used to analyze survival, growth and tree structural traits that define timber quality in plantation forestry. Several provenances performed well with re- spect to height increment, stem crookedness, mortality, and the tendency to produce double stems and lateral branches in the lower or upper part of the stem. Results showed higher survival rates for 'Brumov-Sidonie' and ‘Val di.Sella’ from Czech Republic and Italy respectively. No difference was found be- tween provenances in basal area increment (or diameter), but a good perfor- mance for native provenance ‘Torup’ from Sweden in height increment was found. The Austrian provenance ‘Hinterstoder’ showed the lowest stem crookedness. ‘Perche’ provenance fromFrance and ‘Alsted F.413’ from Den- mark had the lowest tendency to develop double stems below 4,5 m. Prove- nances 'Farchau (SH)' and 'Urach (BW)' both showed the lowest tendencyto develop double stems above 4,5 m on the stem. Tree tendency to develop lateral branches below 4,5 m was lowest for 'Farchau (SH)' provenance from Germany. No significant differences were found between provenances for the frequency of lateral branch divisions above 4,5 m on the stem. The results show that even though beech can be considered a plastic species with a good adaptive response to varying environmental conditions, the genetic background has an important role in shaping stand development. Establishment of specific beech provenances can lead to better quality development in Southern Sweden and should be considered.